Applications of genetic manipulation - Gartlsn, K. M. A. (London : Greenwich University Press, 1900)
This program addresses an example of the commercial exploitation of gene manipulation by combining aspects of molecular biology and cloning techniques with the principles of plant biotechnology to give a herbicide resistant plant
Editor: Dr. J. S. Gartland
System requirements: Hardware requirement, PC with a 20 MHz - 386 processor, 2 MB RAM, 16 colour VGA (640 X 480), hard disk and a mouse. This is a minimum requirement, altough clearly the performance will be improved with more RAM and a higher specification processor. The program requires 6.0 MB free disk space (including the runtime file). Software requirements, the windows based program is supplied in compressed format on two 3.5'' HD disks for use on stand - alone PCs or PC networks. PC run under DOS 3.3 and windows 3.0
Keywords: Genetics; Biochemical genetics